A unique metamaterial inspired star-slot UWB antenna with soft surface ground - Umair, Hassan; Uddin, M. Jasim; Ullah, Mohammad Habib; Latef, Tarik Abdul; Wan Mahadi, Wan Nor Liza; Othman, Mohamadariff (Taylor & Francis, 2020)
A metamaterial (MTM) inspired star-slot planar microstrip line fed ultra-wideband (UWB) antenna having a soft-surface ground structure is presented in this paper. The proposed antenna comprises periodically repeated star-slot unit cells on patch (radiating) side. This feature helps achieve an UWB from 4.0 to 16.2 GHz. Back lobe radiation is suppressed when the ground metallic part is partially replaced by periodic square-shaped cross-slot soft-surface unit cells. The dispersion relation exhibits a wide bandgap in the resonance frequency regions. The backward wave displays a balanced condition when series and shunt frequencies are equivalent (ωse = ωsh), whereas it displays an unbalanced condition when they are not (ωse ≠ ωsh). The periodic star rings etched on the metal patch enhance bore sight gain to a maximum of 8 dBi at 9.2 GHz. The antenna is fabricated on a Duroid substrate with overall dimensions of 27.00 × 31.40 × 1.57 mm3 with a 10.0 GHz of the resonant frequency. The numerical and experimental results verify the proposed artificial metamaterial design structure that matches the theory. © 2020, © 2020 Taylor & Francis.